Luminescence lifetimes in natural quartz annealed beyond its second phase inversion temperature. (October 2015) - Chithambo, M.L.
Abstract: The influence of annealing, irradiation dose, preheating and measurement temperature on luminescence lifetimes has been studied in quartz annealed at 1000 °C. The measurements were supplemented by studies on quartz annealed at 900 and 800 °C. Lifetimes increase with dose as well as with temperature and duration of annealing between 800 and 1000 °C. Preheating produces the same effect. The changes are accounted for in terms of hole-transfer from the non-radiative luminescence centre to and between radiative centres. The influence of measurement temperature on lifetimes depends on whether the stimulation is carried out from ambient to 200 °C or otherwise. This result is unlike that in quartz annealed at or below 500 °C where lifetimes are independent of the direction of heating. In particular, lifetimes decrease monotonically when measurements are made from 20 to 200 °C but not when recorded from 200 to 20 °C. The latter produces a pattern resembling that in quartz annealed up to 500 °C. The results are concluded as evidence of thermal effects on separate luminescence centres. In support of this, different values of the activation energy for thermal quenching were found for each supposed luminescence centre. The change of the corresponding luminescence intensity with temperature is also qualitatively consistent with this notion. Highlights: Luminescence lifetimes in natural quartz annealed beyond its second phase inversion temperature is reported. Lifetimes increase with dose, annealing between 800 and 1000 °C, and preheating. Lifetimes under stimulation temperature are affected by direction of heating. Changes are accounted for in terms of hole-transfer luminescence centres.